Mobile Learning Support with TELD to Facilitate in Learning Environments - Rahmi, Juhaidatur; Wibawa, Basuki; Khaerudin, (International Journal of Psychosocial Rehabilitation, 2020)
Mobile learning application is learning trends that integrate mobile technology advances the benefits of education by utilizing internet access as a communication tool to disseminate information. Mobile learning applications in general are able to improve the results of the learning process by changing students learning habits and learning methods. Through a pedagogical approach to methodology of Teaching by Example and Learning by Doing (TELD) has present to reinforce dynamic interactions and provide instruction how to time integrate and harnees teaching for students. This emerging 21st century conception the principle that learning can be done from anywhere, anytime and anyhow-learning in formal education can be held effectively and efficiently should it, is done in a systematic and holistic way. This article purposes a strategic design mobile learning for effective mobile learning implementation. A courseware approach is being selected as vehicle to conduct learning activities within m-learning environment.